Feature extraction of using statistical spatial methods for content based medical image retrieval - Ergen, Burhan; Baykara, Muhammet (My University, 2010)
Content based image retrieval systems are used widespread for general purpose image archiving, and the developments are still continued it. But it is not widely used for archiving medical images. In presented, it is examined the retrieval efficiency rate of statistical spatial methods used for feature extraction in general purpose images. The investigated algorithms depend on GLCM and GLRLM accepted as spatial methods. The results obtained in this study shows that queries based on statistics obtained from GLCM are more satisfier. ©2010 IEEE.
İçerik tabanli tibbi görüntü erişimi için i?statistiksel uzaysal alan metotlari kullanarak özellik çikarilmasi
2010 15th National Biomedical Engineering Meeting, BIYOMUT2010 -- 21 April 2010 through 24 April 2010 -- Antalya -- 80917
Keywords: Biomedical engineering; Feature extraction; Image retrieval; Content based image retrieval systems; Content based medical image retrieval; General purpose; Medical images; Retrieval efficiency; Medical imaging